The genus Pluteus (Basidiomycota, Agaricales, Pluteaceae) from Tafea Province, Republic of Vanuatu - Del Rosario, Jonathan A.; Perry, Brian A. (Phytotaxa, 2025)
Twenty-three species of the genus Pluteus are newly reported from Tafea Province of the Republic of Vanuatu, a subtropical island archipelago country in the South Pacific located northeast of Australia and equidistant north of New Caledonia, southeast of the Solomon Islands, and west of Fiji. These taxa consist of seven new distributional reports, six tentative identifications, one nom. prov., and nine species, including one form, that are new to science, viz., Pluteus vanuatuensis, P. vanuatuensis var. ramacystidiatus, P. wahei, P. aureofuscus, P. ornatocystidiatus, P. eugraptoides, P. lalepiorum, P. presleyi, and P. tatafuensis. Species level delimitations are based on comprehensive morphological analysis and phylogenetic reconstruction based upon DNA sequence data (ITS or tef1). Evolutionary and biogeographic relationships of the newly generated specimens were examined with molecular-based phylogenies of the three currently accepted infrageneric sections of Pluteus: sect. Pluteus, sect. Hispidoderma, and sect. Celluloderma, based on a global sampling. ITS, tef1, and combined molecular- based phylogenies were constructed to examine the species delimitations of one new species. Comprehensive descriptions, illustrations of relevant micromorphological features, color photographs, comparison to allied taxa, and a dichotomous key to aid in identification are provided.